PENGARUH SOCIAL MEDIA MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI : Studi Kasus: E-Commerce Shopee - Yantho, Vincent; Wilis, Ratih Anggoro (Media Mahardhika, 2024)
In 2023, Shopee secures the top spot for the highest web traffic and online transactions in Indonesia. It's important to consider that Shopee's position as the most favored online store among consumers might face challenges from its competitors. One of the key issues impacting the purchasing interest of Shopee's customers is the competitive landscape within the e-commerce, particularly in terms of the diverse marketing strategies every firm employs. This research seeks to explore how Social Media Marketing and Online Customer Review affect purchase interest within the Shopee E-commerce. The study follows an explanatory approach and employs quantitative data. Accidental sampling is the technique used for selecting participants. The research focuses on students majoring in management at Asia Cyber University between 2020 and 2022, totaling 1.243 individuals. The sample size consisted of 92 management students at Asia Cyber University between 2020 and 2022. The data examination involved multiple linear analysis. The result reveals that collectively, Social Media Marketing and Online Customer Review significantly impact purchasing readability in Shopee. Specifically, Social Media Marketing has a substantial and positive influence on purchasing interest, then Online Customer Review also exhibit a significant and positive influence on the purchasing readability of Management Students in Asia Cyber University within Shopee Marketplace.